Chasing Theory with Technology: A Quest to Understand Understanding. Issue 5 (3rd July 2021) - McNamara, Danielle S.
ABSTRACT: An overarching motivation driving my research has been to further our theoretical understanding of how readers successfully comprehend challenging text. This article describes the theoretical origins of this research program and my quest to understand comprehension processes through the use of technology. Coh-Metrix was developed to measure, and in turn facilitate, manipulations of text cohesion and text ease. iSTART was developed to provide students with instruction and practice on how to explain text and more effectively make use of limited prior knowledge. In addition, we have developed technologies to measure and change writing quality, relations between ideas, and emerging text comprehension. More recently, our attention has turned to comprehension of multiple documents. Understanding relations between documents and how comprehension emerges when reading multiple sources is important educationally and socially, where the internet provides a continuous stream of reliable and unreliable sources. Across these topics, my collaborators and I have conducted numerous experimental studies, but a central theme to my work has been the use of technology. This article describes these technologies, including natural language processing, game-based tutoring systems, and computational simulations; how they were informed by theory; and how they have informed my theoretical and practical understandings of language, comprehension, social interactions, and cognition as multilayered and multidimensional within what I refer to as the M&M Framework.